2019
DOI: 10.1111/jgs.15821
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Intensive Dementia Caregiver Training Model on Knowledge and Self‐Competence: The Improving Caregiving for Dementia Program

Abstract: The funders had no role in the study design, methods, subject recruitment, data collections, analysis, and preparation of the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
(12 reference statements)
2
1
0
1
Order By: Relevance
“…This study found a significant increase in the knowledge score for the experimental group following the modified TTSC program compared to the control group in week 8 and week 20. This result was consistent with those of other researchers who employed multicomponent programs for dementia caregivers [ 31 , 32 , 33 ]. The group education activity in this study was similar to boot camp on knowledge [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study found a significant increase in the knowledge score for the experimental group following the modified TTSC program compared to the control group in week 8 and week 20. This result was consistent with those of other researchers who employed multicomponent programs for dementia caregivers [ 31 , 32 , 33 ]. The group education activity in this study was similar to boot camp on knowledge [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…This result was consistent with those of other researchers who employed multicomponent programs for dementia caregivers [ 31 , 32 , 33 ]. The group education activity in this study was similar to boot camp on knowledge [ 31 , 32 ]. Moreover, the multicomponent of this study increase knowledge level as well as the multicomponent psychosocial intervention program [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…De igual forma, los videos han aumentado los conocimientos de pacientes con ACV (14) , cuidadores de pacientes con asma (15) , niños con epilepsia (16) y pacientes en unidades de cuidados intensivos (17) . Por otro lado, el entrenamiento presencial entre los mismos cuidadores o con actores que hacen de pacientes, sumado a retroalimentación por parte del profesional de salud, han incrementado el conocimiento y autocompetencia de cuidadores de pacientes con demencia (18) , y la autoeficacia y preparación para el cuidado de los cuidadores de pacientes con cáncer (19) , de igual manera, los conocimientos y prácticas reportadas en cuidadores de pacientes con ACV (20) .…”
Section: Mensajes Clave Introducciónunclassified
“…Research demonstrates that caregiver competence for dealing with challenges related to dementia caregiving can be increased via education and training (Van't Leven et al, 2013). For example, UCLA's Improving Caregiving for Dementia (I-CareD) Caregiver Bootcamp, an intensive one-day training for dementia caregivers, has demonstrated efficacy for improving caregiver knowledge and perceived selfcompetence as a caregiver (Tan et al, 2019).…”
Section: Implications For Increasing Dementia Caregiver Well-beingmentioning
confidence: 99%